Percutaneous Tibial Nerve Stimulation vs Sham Stimulation for Fecal Incontinence in Women: NeurOmodulaTion for Accidental Bowel Leakage Randomized Clinical Trial. (April 2022) - Zyczynski, Halina M.; Richter, Holly E.; Sung, Vivian W.; Lukacz, Emily S.; Arya, Lily A.; Rahn, David D.; Visco, Anthony G.; Mazloomdoost, Donna; Carper, Benjamin; Gantz, Marie G.; ,
Abstract : INTRODUCTION: To determine whether percutaneous tibial nerve stimulation (PTNS) is superior to sham stimulation for the treatment of fecal incontinence (FI) in women refractory to first-line treatments. METHODS: Women aged 18 years or older with ≥3 months of moderate-to-severe FI that persisted after a 4-week run-in phase were randomized 2:1 (PTNS:sham stimulation) to 12 weekly 30-minute sessions in this multicenter, single-masked, controlled superiority trial. The primary outcome was change from baseline FI severity measured by St. Mark score after 12 weeks of treatment (range 0–24; minimal important difference, 3–5 points). The secondary outcomes included electronic bowel diary events and quality of life. The groups were compared using an adjusted general linear mixed model. RESULTS: Of 199 women who entered the run-in period, 166 (of 170 eligible) were randomized, (111 in PTNS group and 55 in sham group); the mean (SD) age was 63.6 (11.6) years; baseline St. Mark score was 17.4 (2.7); and recording was 6.6 (5.5) FI episodes per week. There was no difference in improvement from baseline in St. Mark scores in the PTNS group when compared with the sham group (−5.3 vs −3.9 points, adjusted difference [95% confidence interval] −1.3 [−2.8 to 0.2]). The groups did not differ in reduction in weekly FI episodes (−2.1 vs −1.9 episodes, adjusted difference [95% confidence interval] −0.26 [−1.85 to 1.33]). Condition-specific quality of life measures did not indicate a benefit of PTNS over sham stimulation. Serious adverse events occurred in 4% of each group. DISCUSSION: Although symptom reduction after 12 weeks of PTNS met a threshold of clinical importance, it did not differ from sham stimulation. These data do not support the use of PTNS as conducted for the treatment of FI in women.